STUDI KELAYAKAN PENGEMBANGAN BISNIS PETERNAKAN LEMBU DAN MANAJEMEN KEUANGAN PARA PETERNAK LEMBU DI DESA/NAGORI BAHJOGA KEC. JAWA MARAJA BAHJAMBI KAB. SIMALUNGUN - Lusi Elviani Rangkuti; Farida Khairani Lubis; Jalilah Ilmiha (Jurnal Pengabdian Mitra Masyarakat, 2021)
This community service is conducted in the village village/Nagori Bahjoga District Java Maraja Bah Jambi Simalungun District. The purpose of this community service in general is to help advance the business of cattle farming of the villagers. This activity is carried out by conducting a business feasibility study on livestock business activities that have been conducted so far by cattle farmers in the Village / Nagori Bahjoga.